Europe's wicked legitimacy crisis: the case of refugees. Issue 4 (7th June 2018) - Murray, Philomena; Longo, Michael
Abstract: The European Union's response to the current and persistent – if not wicked – refugee crisis has exposed a new legitimacy challenge. Characterised by interstate bickering and undignified competition for the most draconian measures, the crisis brings to the fore many inherent tensions of the EU which cannot be easily reconciled. The crisis has revealed the many shortcomings of EU governance. Deficits of leadership and solidarity and the rise of xenophobic politics across many member states exploit growing populism with pronounced effect. This multi-dimensional problem, so resistant to a distinct solution, underscores the EU's instability in a number of ways: its foundational values have lost resonance; its institutional inadequacies have become more apparent; its leadership and agenda-setting power have been noticeably weakened. Ultimately, the EU is no longer perceived as a problem-solver, a fact that inherently tests the legitimacy of a system that was created to solve problems.